Psychological symptoms are associated with screen and exercise time: a cross-sectional study of Chinese adolescents - Zhang, Feng (BMC Public Health, 2020)
BACKGROUND: Mental disorders among adolescents have become a worldwide public health problem. This study aimed to estimate the best combination of exercise time and screen time to promote the mental health of Chinese adolescents. METHODS: Participants included 7200 Chinese adolescents aged 13–18 years from six regions of China. Screen and exercise time data were collected via a self-rated questionnaire. Psychological symptoms (e.g., often feeling depressed, school-weary) were evaluated with the “Multidimensional Sub-health Questionnaire of Adolescents”. Chi-squared tests and logistic regression analysis were conducted to investigate the differences in and correlations among screen time, exercise time, and psychological symptoms. RESULTS: The overall detection rate of psychological symptoms among Chinese adolescents was 21.4% (22.1% for boys and 20.6% for girls). Psychological symptom detection rates were lowest among adolescents with 1–2 h/d of screen time (19.5%) and those with 30–60 min/d of exercise time (17.3%). Screen time > 2 h/d (OR = 1.38, P < 0.001) and exercise time < 30 min/d (OR = 1.62, P < 0.001) were positively correlated with psychological symptoms. CONCLUSION: Screen and exercise time are associated with psychological symptoms in Chinese adolescents. A combination of 1–2 h/d of screen time and 30–60 min/d of exercise time is provided as a reference for better mental health.